Dexketoprophenum as a tool for perioperative analgesia - S V Sokologorsky (IP Berlin A.V., 2014)
The problem of postoperative pain relief, despite the constant conductivity of research for best practices and technologies, remains far from being solved. The spectrum of analgesics available in the arsenal of anesthesiologists and other surgical specialties is not always efficiently and expediently used. Traditional use of opioid analgesics in the postoperative period is often difficult and worsens the results of surgical treatment. Nonsteroidal anti-inflammatory drugs, possessing both analgesic and anti-inflammatory features, can be successfully incorporated into the multimodal scheme of postoperative analgesia and used as a component of intensive therapy. The article provides an overview of the literature on dexketoprophenum use - S (+) - ketoprophenum - perioperative, examining the scheme of its use as a component of multimodal analgesia.